Clinical presentation, magnetic resonance imaging characteristics, and short-term outcome of deep surgical site infection following thoracolumbar decompressive spinal surgery for intervertebral disc herniation in dogs - To, Alexandra Y K; Cherubini, Giunio Bruto; Caine, Abby (Frontiers in Veterinary Science, 2025)
ObjectiveTo characterize the clinical presentation, magnetic resonance imaging (MRI) features, and short-term outcomes of deep surgical site infection (SSI) following thoracolumbar (TL) decompressive spinal surgery for intervertebral disc herniation (IVDH) in dogs.MethodRetrospective, single-center observational study of dogs that underwent postoperative MRI and were diagnosed with culture-confirmed deep SSI after TL decompressive spinal surgery between 2017 and 2021. Medical records and MRI studies (pre- and postoperative) were reviewed.ResultsNineteen dogs were diagnosed with deep SSI among 1723 thoracolumbar decompressive surgeries (incidence: 1.1%). The median time to SSI diagnosis was 7 days (range, 2–38 days). Clinical signs included spinal hyperesthesia (100%) and neurological deterioration (36.8%). MRI revealed bilateral epaxial muscle hyperintensity (66.7%), fascial plane tracking (100%), and multifocal signal voids (89.5%) as possible differentiating features. Staphylococcus spp. were the most common isolates (52.6%). All dogs survived to discharge, with 73.7% being ambulatory; short-term follow-up, available in 14/19 cases, showed resolution of clinical signs.Conclusion and clinical significanceDeep SSI after TL spinal decompression typically presents within 2 weeks with spinal hyperesthesia. Several MRI patterns may be associated with SSI. Despite rare complications, the majority of cases had favorable short-term outcomes.